Applying Project Management to Establish an Academic Health System: A Participatory Action Research - Josephine, Jodie; Tj, Hery Winoto; Fushen (Jurnal Kedokteran Meditek, 2025)
Introduction: Academic Health Systems (AHS) integrate healthcare, education, and research to enhance medical training and patient care. However, initiating AHS in institutions without an existing framework presents challenges in aligning stakeholder expectations and organizational structures. Purpose: This study aims to initiate and establish an appropriate AHS model for Ukrida AHS through Project Management (PM) principles and highlight the importance of PM principles in healthcare organizations. Methods: A qualitative research design was employed using semi-structured interviews with six key stakeholders. Thematic analysis identified recurring patterns in stakeholder perceptions, expectations, and challenges regarding AHS implementation. Data triangulation through a Focus Group Discussion (FGD) refined the findings. Results: The findings are categorized into three phases: Inquiry, which identified three key themes—stakeholder perceptions of their organization, understanding of AHS, and perceived benefits and challenges; Action, which translated these insights into concrete steps, including goal-setting, developing a Gantt chart, and an AHS model; and Reflection, which assessed the research process and emphasizing the benefits of using PM principles in healthcare organizations. Conclusion: Integrating PM with PAR facilitated AHS initiation at Ukrida, revealing benefits, challenges, and key priorities: leadership alignment, financial sustainability, faculty development, stakeholder collaboration, and data systems to ensure long-term success and scalability.